Magnetic phosphorylated lignocellulosic fibers: A hybrid material for water purification – Part I material synthesis - Sayadi, Sabrine; Brouillette, François (Colloids and surfaces. A, Physicochemical and engineering aspects)
Magnetic functionalized phosphorylated papers were synthesized using a simple and efficient method. Several characterizations were carried out to determine the structure, morphology and types of interaction between the phosphorylated cellulose fibers (PKF) and the magnetic particles. The results show excellent swelling of the cellulose structure, without altering its morphology, indicating the robustness of the method and the preservation of the fundamental properties of the fibers. X-ray diffraction confirmed the incorporation of Fe₃O₄ into the cellulose matrix, as shown by characteristic reflections of magnetite and cellulose. The broadening of Bragg peaks indicated the formation of spinel-structured Fe₃O₄ particles remaining strongly attached to fibers even after extensive washing because of strong cellulose-magnetite interactions. The synthesis approach preserved the structural integrity of the fibers while enhancing their specific surface area and accessibility. Surface energy analysis revealed a high adhesion energy between PKF and Fe₃O₄, preventing particle agglomeration and ensuring homogeneous distribution. The presence of Fe₃O₄ led to an overall improvement in mechanical properties due to its uniform dispersion within the fibrous matrix. Thermogravimetric analysis (TGA) showed the high thermal resistance of both PKF and PKF-Fe₃O₄ composite. To assess the long-term stability of the magnetic phosphorylated paper, iron leaching tests were performed at different pH levels. The composite showed minimal Fe release, with iron concentrations remaining below 0.2 mg/L for pH values above 3, indicating low environmental risk. These results confirm that PKF-Fe₃O₄ composite is a robust, stable, and thermally resistant material, making it a promising candidate for advanced applications requiring magnetic cellulose-based composites. [Display omitted] •Phosphorylated kraft fibers were modified with magnetite to create hybrid composites.•The material exhibits flame retardancy and enhanced mechanical strength.•Minimal iron leaching ensures structural stability in various conditions.•Robust synthesis preserves cellulose morphology and enhances composite performance.•High affinity between fibers and magnetite promotes efficient composite formation.